Ethanol Extract of Cissus quadrangularis Enhances Osteoblast Differentiation and Mineralization of Murine Pre‐Osteoblastic MC3T3‐E1 Cells. Issue 3 (15th June 2016) - Tasadduq, Raazia; Gordon, Jonathan; Al‐Ghanim, Khalid A.; Lian, Jane B.; Van Wijnen, Andre J.; Stein, Janet L.; Stein, Gary S.; Shakoori, Abdul Rauf
Abstract : Traditional medicinal literature and previous studies have reported the possible role of Cissus quadrangularis (CQ) as an anti‐osteoporotic agent. This study examines the effectiveness of CQ in promoting osteoblast differentiation of the murine pre‐osteoblast cell line, MC3T3‐E1. Ethanolic extract of CQ (CQ‐E) was found to affect growth kinetics of MC3T3‐E1 cells in a dosage‐dependent manner. High concentrations of CQ‐E (more than 10 μg/ml) have particularly adverse effects, while lower concentrations of 0.1 and 1 µg/ml were non‐toxic and did not affect cell viability. Notably, cell proliferation was significantly increased at the lower concentrations of CQ‐E. CQ‐E treatment also augmented osteoblast differentiation, as reflected by a substantial increase in expression of the early osteoblast marker ALP activity, and at later stage, by mineralization of extracellular matrix compared to the control group. These findings suggest dose‐dependent effect of CQ‐E with lower concentrations exhibiting anabolic and osteogenic properties. J. Cell. Physiol. 232: 540–547, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Ethanolic extract of a herb, Cissus quadrangularis (CQ‐E) has dose dependent effect on the differentiation of murine pre‐osteoblast MC3T3‐E1 cells. Lower concentrations exhibit anabolic and osteogenic properties. We have demonstrated that changes in cellular activity during osteogenesis is accompanied by corresponding changes in expression of osteoblast differentiation specific marker genes. CQ‐E has the potential to be used for healing fractures and to prevent and treat osteoporosis.